Cheating in networked computer games: a review - Webb, Steven; Soh, Sieteng (Association for Computing Machinery (ACM), 2007)
The increasing popularity of Massively Multiplayer Online Games (MMOG) - games involving thousands of players participating simultaneously in a single virtual world - has highlighted the scalability bottlenecks present in centralised Client/Server (C/S) architectures. Researchers are proposing Peer-to-Peer (P2P) architectures as a scalable alternative to C/S; however, P2P is more vulnerable to cheating as it decentralises the game state and logic to un-trusted peer machines, rather than using trusted centralised servers. Cheating is a major concern for online games, as a minority of cheaters can potentially ruin the game for all players. In this paper we present a review and classification of known cheats, and provide real-world examples where possible. Further, we discuss counter measures used by C/S architectures to prevent cheating. Finally, we discuss several P2P architectures designed to prevent cheating, highlighting their strengths and weaknesses.